Trophy Hunting Contracts: Unenforceable for Reasons of Public Policy - Dellinger, Myanna (Columbia Journal of Environmental Law, 2019)
Cecil the Lion. The name speaks for itself: famed alpha male lion lured outside a Zimbabwean national park to be shot for “sport” by American dentist Walter Palmer in the summer of 2015. Palmer reportedly shot Cecil with a crossbow, then stalked the lion for forty hours before finally killing and beheading it. Palmer reportedly paid over fifty thousand U.S. dollars to a local hunting guide and landowner for the hunt. In such “trophy hunting” agreements, wealthy individuals, typically from the Global North, pay locals such as guides or landowners, often in the Global South, to assist with the planned hunt of rare—if not outright threatened or endangered—species such as lions, polar bears, black rhinoceroses, and giraffes for a fee as a private contractual arrangement. In other cases, hunters obtain government permits to kill and import a rare animal. Allegedly, trophy hunts contribute to local economies and can help raise money and awareness for species conservation. However, serious doubt has arisen about the effectiveness of trophy hunts on society’s ultimate goal—undisputed by trophy hunters—of conserving rare species. The “shadowy subculture” that trophy hunting has been said to be is one that attempts to make the unacceptable sound acceptable under the guise of euphemisms and questionable facts as will be demonstrated in this Article. While such discussions continue, more and more of the very last few specimens of several rare species are killed for, in effect, fun. As a society, we cannot allow trophy hunting of wild, rare animals to proceed given the uncertainty surrounding the effects of the practice and the reprehensibility of it to society. Contracts that are considered “unsavory,” “undesirable,” “at war with the interests of society,” or “in conflict with the morals of the time” may be declared unenforceable for reasons of public policy regardless of whether or not any underlying legislation provides that the contractual conduct is illegal. Allowing wealthy individuals to kill some of the very last few specimens of rare species has become so distasteful to so many members of the general public that the time has come for courts to declare such contracts unenforceable for reasons of public policy. This Article demonstrates how this may be accomplished. The Article also examines the wildlife-protective capabilities of the public trust doctrine and the closely related state ownership of wildlife doctrine. These doctrines add further weight to the contractual argument, but also operate as stand-alone protective doctrines in lawsuits against government entities. To be able to present any of these arguments to a court of law, standing is a hurdle, but one that can be overcome. This Article highlights how this might be done.